Additive Manufacturing of High-Performance Ti-Mo Alloys Used on a Puncture Needle: The Role of Linear Energy Density in Microstructure Evolution and Mechanical Properties - Xuesong Dai; Yue Sun; Jitai Han (Crystals, 2025)
This study involved the preparation of dense Ti-10wt.%Mo alloys using selective laser melting (SLM) with a powder combination of pure titanium (Ti) and pure molybdenum (Mo). Integrating temperature stress numerical simulations and actual data elucidates the correlation between linear laser energy density and residual stress. The impact of linear energy density on the surface roughness, densification behavior, microstructural development, and mechanical properties of SLM-processed Ti-10Mo components was also examined. As linear energy density diminished from 0.125 J/mm to 0.233 J/mm, surface roughness reduced from 18.2 μm to 4.4 μm, while relative compactness increased from 94.9% to 99.8%, respectively. It is necessary to reduce the friction between the puncture needle or implant needle and human tissue, enhancing comfort and precision. The microstructural investigation revealed that SLM-processed Ti-10Mo alloys consist of a phase combination of hexagonal tight-packed (hcp) α-Ti and body-centered cubic (bcc) β-Ti, with heterogeneous conchoidal microstructures found in the samples. Furthermore, as the laser energy input increased, Mo powder particles were mostly fully melted, leading to a significant rise in the microhardness value. The as-built Ti-10Mo alloys exhibited a high ultimate tensile strength of 860 MPa and an elongation of 32.9% at a linear laser energy density of 0.15 J/mm, with the fracture morphology indicating a mixed fracture mode mostly characterized by ductile fracture. This research can enhance the prospective bio-application of Ti-Mo alloys.